On Countable Almost Invariant Partitions of G-Spaces - Kharazishvili, A. B. (Ukrains’kyi Matematychnyi Zhurnal, 2014)
For any σ -finite G-quasiinvariant measure μ given in a G-space, which is G-ergodic and possesses the Steinhaus property, it is shown that every nontrivial countable μ-almost G-invariant partition of the G-space has a μ-nonmeasurable member.